Salaman and Absal in Abd al-Rahman Jami - Halilović Tehran (Kom: Časopis za Religijske Nauke)
Abd al-Rahman Jami was a renowned gnostic and writer from the 15th century, known and respected throughout the Islamic world at the time. He was not a court poet, but he had close relations with the leaders of political and social life, especially with Amir Ali-Shir Nava'i, Bayqara's vizier and also a prominent poet. Jami belonged to the Sufi Naqshbandi Order and advocated Ibn Arabi's ideas in the field of doctrinal gnosis. In the second chapter of Haft Ourang Jami told the story of Salaman and Absal. There are two versions of the story of Salaman and Absal in Islamic texts. There is a story mentioned by the grandiose Islamic philosopher Ibn Sina in the book Isharat and it is narrated and interpreted by Nasir al-Din Tusi in his commentary on this book. In Ibn Sina's story, Salaman and Absal are two brothers. As Ibn Sina states, Salaman is a symbol of the human soul and Absal is an indicator of the level of gnostic knowledge. The second version is a Hermetic story translated from Greek into Arabic by Hunayn ibn Ishaq and first told by Jami in a poem of over a thousand lines. In this story, Salaman is the king's son, in love with his nurse, Absal. Since the king and his sagacious adviser oppose their love, Salaman leaves the city but fails to persuade his father to accept his choice. Absal's death causes great spiritual pain to Salaman. The king's sagacious adviser helps Salaman recognize the truth of eternal love in the image of Venus, the symbol of love in Persian literature. Nasir al-Din Tusi claims that Absal, in this version of the story, is a symbol of material life, which is why he disagrees with the idea presented by Ibn Sina in Isharat. The subject of this work is Jami's gnostic view on the development of Salaman's personality. Although Jami repeats the interpretation that Tusi presents in the commentary on Isharat, his approach to the story is significantly different. Jami's extensive knowledge of Ibn Arabi's doctrinal gnosis makes this story one of Jami's finest literary and gnostic works.